Nepotism, incentives and the academic success of college students - Gevrek, Deniz; Gevrek, Z. Eylem (My University, 2010)
This study investigates the role of parent-owned businesses on children's college success and post-college aspirations by using a unique data set from a private university in Turkey. The data set matches college students' administrative records with survey responses. The presence of self-employed parents and family businesses has a strong negative association with college success even after accounting for observed ability, parental background, and various individual characteristics. An explanation for the lower GPAs of the children of self-employed parents is that in the presence of parent-owned businesses students have a larger set of post-graduation options and are more likely to plan on becoming self-employed due to intergenerational transfer of self-employment. Hence, these students may not exert as much effort in acquiring the task-specific career-oriented human capital taught in college. In line with expectations, we find that the children of self-employed parents are more likely to have entrepreneurial intent and are less likely to plan to attend graduate school.
Keywords: College success; Self-employment; Family businesses; Nepotism; 330